2018
DOI: 10.1097/eja.0000000000000833
|View full text |Cite
|
Sign up to set email alerts
|

Deep neuromuscular blockade and surgical conditions during laparoscopic ventral hernia repair

Abstract: ClinicalTrials.gov, NCT02247466.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Further, deep NMB with lower intra-abdominal pressure were reported to provide few cardiopulmonary benefits during laparoscopic colorectal surgery [ 90 ]. Moreover, deep NMB did not improve the surgical view during laparoscopic ventral hernia repair and showed benefits only during suturing of the hernial defect [ 91 ]. However, studies on post-surgical outcomes are recent.…”
Section: Recent Clinical Interests Regarding Sugammadexmentioning
confidence: 99%
“…Further, deep NMB with lower intra-abdominal pressure were reported to provide few cardiopulmonary benefits during laparoscopic colorectal surgery [ 90 ]. Moreover, deep NMB did not improve the surgical view during laparoscopic ventral hernia repair and showed benefits only during suturing of the hernial defect [ 91 ]. However, studies on post-surgical outcomes are recent.…”
Section: Recent Clinical Interests Regarding Sugammadexmentioning
confidence: 99%
“…1 , PRISMA study selection flow chart), 22 papers were included in the review ( Table 4 ). We identified 12 that used propofol as primary anaesthetic agent, 6 , 10 , 19 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 of which six found a benefit of deep neuromuscular block on surgical working conditions, 6 , 10 , 19 , 25 , 26 , 27 and six did not. 28 , 29 , 30 , 31 , 32 , 33 In addition, 10 studies were identified that used an inhalation agent.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 12 that used propofol as primary anaesthetic agent, 6 , 10 , 19 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 of which six found a benefit of deep neuromuscular block on surgical working conditions, 6 , 10 , 19 , 25 , 26 , 27 and six did not. 28 , 29 , 30 , 31 , 32 , 33 In addition, 10 studies were identified that used an inhalation agent. 14 , 15 , 16 , 17 , 18 , 20 , 21 , 22 , 23 , 24 Seven out of these 10 studies reported a benefit of deep neuromuscular block during inhalation anaesthesia on surgical working conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it is in line with the ongoing controversial debate on neuromuscular blockade to improve surgical conditions. Whereas many publications present significantly better operating conditions during deep NMB, compared to a light block [3,4,8,14,[17][18][19], several other authors found no differences [1,15,20]. Park et al describe inconsistent results and state that "further studies are required to address the heterogeneity and power shortage demonstrated by the trial sequential analysis", in a previously published review [21].…”
Section: Discussionmentioning
confidence: 99%